Simone de Beauvoir : une philosophie de la pédagogie ? - Levéel, Eric (Sapere Aude, 2014)
Simone de Beauvoir’s teaching in the 1930s is a fairly neglected area of investigation or it is relegated to the margin of Beauvoirian Studies. The publication in 2012 of an original text entitled “La Princesse de Clèves à Belleville” by Suzanne (sic) de Beauvoir – discovered by Tiphaine Martin and identified as belonging to Simone de Beauvoir by her adopted daughter – dating back from 1927 and depicting her experience as a volunteer-teacher in working-class Belleville in Paris in 1926 has forced a reinterpretation of what teaching meant to Beauvoir in the 1930, but also in the 1930s. By a close reading of primary sources and with the help of secondary sources, can one define a Beauvoirian pedagogy? Can one find a philosophy of teaching in Beauvoir’s thoughts? Furthermore, can one determine the importance, or lack thereof, of teaching in Simone de Beauvoir’s existence? Finally, can one offer an explanation as to why teaching was seen as a contingent occupation by her beyond the obvious routine attached to it? A atuação de Simone de Beauvoir como professora em 1930 é uma aspecto bastante negligenciado pelos estudiosos ou que tem ficado à margem dos Estudos Beauvoirianos. A publicação em 2012 de um texto original intitulado “La Princesse de Clèves em Belleville", de Suzanne (sic) de Beauvoir - descoberto por Tiphaine Martin e identificado como sendo de Simone de Beauvoir por sua filha adotiva –, texto escrito em 1927, no qual se representa a experiência de Beauvoir como professora voluntária, ministrando aulas em Belleville, Paris, em 1926, forçou uma reinterpretação do que a docência significava para ela em 1930 e na década de 1930. Por meio de uma leitura atenta das fontes primárias e com a ajuda de fontes secundárias, pode-se definir uma pedagogia beauvoiriana? Pode-se encontrar uma filosofia da educação nos pensamentos de Beauvoir? Além disso, pode-se determinar a importância (ou o contrário) da docência na existência de Simone de Beauvoir? Finalmente, ultrapassando o argumento da óbvia rotina inerente a esse tipo de atividade, pode-se oferecer uma explicação de por que a docência era vista por Beauvoir como uma ocupação contingente?